Pengaruh Critical Thinking, Kolaborasi dan Resiliensi Matematika terhadap Hasil Belajar Matematika Siswa Kelas VII SMPN 5 Banguntapan - Dwi Etikasari; Tri Astuti Arigiyati; Irham Taufiq (Wacana Akademika: Majalah Ilmiah Kependidikan, 2025)
This study aims to determine the positive and significant effect of critical thinking, collaboration, mathematical resilience on mathematics learning outcomes partially and simultaneously. The population of this quantitative correlational research method was all seventh grade students of SMPN 5 Banguntapan, with sample of 61 students (VII A, C) selected through cluster random sampling. The research instruments were a mathematical collaboration and resilience questionnaire, a collaboration observation sheet, and a critical thinking test that were tested to be valid and reliable. Data were analyzed using correlation analysis, multiple linear regression, t-test, and F-test that met the prerequisite tests (normality, linearity, multicollinearity). The results showed a positive and significant effect between critical thinking, collaboration, mathematical resilience on students' mathematics learning outcomes, partially (sig. 0.000≤0.05) and simultaneously (29.1%). This study is expected to be a reference for further research related to the effect of critical thinking, collaboration, mathematical resilience on mathematics learning outcomes.